Digital Transformation And Financial Inclusion In Islamic Economics: Ethical Challenges And Policy Implication - Ryandra Adiatma Hartono (PT. Samudra Solusi Profesional, 2024)
The rapid advancement of digital technology has fundamentally reshaped financial systems worldwide, offering new pathways to enhance financial inclusion. Within this context, Islamic economics presents a distinctive framework that integrates ethical principles, risk-sharing mechanisms, and social justice objectives. This article examines the role of Islamic economics in the dynamics of digital transformation and financial inclusion through a qualitative literature-based approach. Drawing upon peer-reviewed international and national academic publications, as well as institutional reports from the World Bank, Bank Indonesia, the Financial Services Authority (OJK), and Statistics Indonesia (BPS), this study synthesizes conceptual, empirical, and policy-oriented insights. The findings indicate that digital financial services such as Islamic fintech, digital Islamic banking, peer-to-peer lending, and crowdfunding for zakat and waqf have significant potential to expand access to Sharia-compliant financial services, particularly among underserved populations. However, the practical realization of this potential remains constrained by several structural challenges, including low Islamic financial literacy, limited public trust, regulatory fragmentation, and unequal digital infrastructure. National evidence from the 2024 National Survey of Financial Literacy and Inclusion (SNLIK) reveals that Islamic financial literacy stands at 39.11%, while Islamic financial inclusion is only 12.88%, highlighting a substantial gap between awareness and actual utilization. This article argues that digital transformation in Islamic finance must be aligned with the objectives of maqasid al-shariah to ensure that technological efficiency does not compromise ethical and social goals. Policy recommendations include strengthening digital Islamic financial literacy programs, enhancing regulatory harmonization for Islamic fintech, promoting collaboration between Islamic banks and fintech firms, and developing inclusive digital payment infrastructures. By integrating technological innovation with Islamic economic principles, Islamic finance can play a strategic role in fostering equitable and sustainable financial inclusion. This study contributes to the growing discourse on digital Islamic economics and provides a conceptual foundation for future empirical research.